The Examination of the Year Effect Based on Cumulative Temperature and Rainfall Curve - Piskolczi, Miklós (Acta Agraria Debreceniensis, 2003)
In order to get to know the numerical differencies of favourable and unfavourable weather conditions, our research lean to 29-years-data (1961-1989) of maize yield of productive area of Hajdúság from which we chose two low (1964, 1976) and two high (1969, 1975) yield yerars. Choosing the years we fitted a linear trend to the time series and the valued data was divided by the realised crop. From the cumlative temperature- and rainfall data calculatd curve concern the period between 01. April and 01. September. The basis was the cumulative value of many years daily average value. The temperature- and rainfall curve of favourable and unfavourable yield with the many years average data was represented on the same scale. In order to numericate the differencies we count the differencies monthly frequency. Based on it became sunder the feature of years. The method used by us ensure possibility to separate the temporal types. It was found that informing the yield the rainfall has main role in this productive area and the temperature has only second role.